Speed of engagement with support generated by a smoking cessation smartphone Just In Time Adaptive Intervention (JITAI) - Felix Naughton (Frontiers Media S.A., 2015)
Background: An advantage of the high portability and sensing capabilities of smartphones is the potential for health apps to deliver advice and support to individuals close in time to when it is deemed of greatest relevance and impact, often referred to as Just In Time Adaptive Interventions (JITAI). However, little research has been undertaken to explore the viability of JITAI in terms of how long it takes users to engage with support triggered by real time data input, compared to scheduled support, and whether context affects response. This paper is focused on Q Sense, a smoking cessation app developed to deliver both Just in Time and scheduled support messages (every morning) during a smoker's quit attempt. The Just in Time cessation support generated by Q Sense is triggered by and tailored to real time context using location sensing. Objectives: To assess: 1) the time to engage with the app after a Just in Time support notification is delivered and whether this is influenced by the context in which the notification was initially delivered, 2) whether the time to engage with the app differs between Just in Time support notifications and scheduled support message notifications and 3) whether findings from objectives 1 and 2 differ between smokers receiving or not receiving NHS smoking cessation support. Methods: Data are from two studies evaluating the use of Q Sense: a feasibility study using an opportunity sample of smokers initiating a quit attempt with Q Sense without NHS cessation support (N=15) and an ongoing acceptability study of smokers receiving NHS smoking cessation support alongside app use (target N=40, recruitment due to be completed end of November 2015). Time elapse between notification generation and the user opening the app will be calculated and compared between message types (Just in Time vs. scheduled messages), contexts (home, work, socialising, other) and samples (receiving or not receiving NHS cessation support) using t-tests and ANOVA. Findings: The results from analyses related to all three objectives will be presented. Preliminary analyses indicate that among feasibility study participants the mean time to engage with the app after a Just in Time support notification was 63.9 minutes (SD 101.8) with 50.0% opening the app within 30 minutes of notification delivery. In comparison, the mean time to engage after a scheduled morning support message notification was 77.8 minutes (SD 124.5) with 34.2% opening the app within 30 minutes of the notification. The extent to which response time varied by context and receipt of NHS cessation support will be presented. Discussion: Understanding engagement with JITAI is essential to inform the content and timing of behavioural support messages delivered in real time in response to real time context. This insight, including how context may interact with engagement, can help guide development work to optimize support delivery.